(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article provides information about the education of Uzbek women in the years after the Second World War. The ideology of the colonial state carried out in the educational system, the process of the Soviet "cultural revolution" event, over-ideologicalizing all aspects of society, especially science and culture, and covering every area of it, and its impact on the current era, education, science an attempt was made to reveal the activities of women in the field of science and the processes of education on the basis of several research data. In addition, the penetration and achievements of women in every field, the example of the life of Khadicha Sulaymanova, is highlighted.